Effect of Wheat Grain Steaming and Washing on Lipase Activity in Whole Grain Flour. Issue 4 (23rd July 2014) - De Almeida, Juliano Luiz; Pareyt, Bram; Gerits, Lien R.; Delcour, Jan A.
ABSTRACT: During whole grain flour (WGF) storage, lipase activity causes partial loss of its functionality and the sensory acceptability of products produced from it. The objective of this research was to evaluate the effect of steaming and washing on lipase activity in (fractions of) wheat. Steam treatment conditions were optimized for wheat grains and their bran, shorts, and flour fractions. Lipase activities were determined colorimetrically, as were peroxidase, endoxylanase, and α‐amylase activities. Steaming grains for 180 s effectively inactivated lipase, peroxidase, endoxylanase, and part of the α‐amylase without gelatinizing starch. The work further demonstrated that lipase is mainly, if not only, located in the bran fraction. Separate bran treatment holds promise for obtaining WGF with reduced lipase activity but without altered functional properties. Washing grains did not reduce WGF lipase activity.